Unsteady Hydromagnetic Heat and Mass Transfer Flow of a Heat Radiating and Chemically Reactive Fluid Past a Flat Porous Plate with Ramped Wall Temperature. (21st August 2013) - Nandkeolyar, R.; Das, M.; Sibanda, P.
Abstract : Unsteady hydromagnetic free convective flow of a viscous, incompressible, electrically conducting, and heat radiating fluid past a flat plate with ramped wall temperature and suction/blowing is studied. The governing equations are first subjected to Laplace transformation and then inverted numerically using INVLAP routine of Matlab. The numerical solutions of the fluid properties are presented graphically while the skin friction and heat and mass transfer coefficients are presented in tabular form. The results are verified by a careful comparison with results in the literature for certain parameter values.